Micronutrient composition and microbial community analysis across diverse landraces of the Ethiopian orphan crop enset. (November 2020) - Tamrat, Solomon; Borrell, James S.; Biswas, Manosh K.; Gashu, Dawd; Wondimu, Tigist; Vásquez-Londoño, Carlos A.; Heslop-Harrison, Pat J.S.; Demissew, Sebsebe; Wilkin, Paul; Howes, Melanie-Jayne R.
Graphical abstract: Highlights: The largest survey to date of variation in enset nutritional composition. Enset is high in Fe, Ca and Zn, and low in Na compared with locally available crops. Concentrations of free amino acids are altered by fermentation. Acetobacter, Lactobacillus and Bifidobacterium mediate fermentation. Microbial community sequencing can be used to detect contamination. Abstract: Enset ( Ensete ventricosum ) is a major starch staple and food security crop for 20 million people. Despite substantial diversity in morphology, genetics, agronomy and utilization across its range, nutritional characteristics have only been reported in relatively few landraces. Here, we survey nutritional composition in 22 landraces from three enset growing regions. We present mineral characterization of enset corm tissue, free amino acid characterization of raw and processed (fermented) tissues and genomic analysis of the microbial community associated with fermentation. We show that compared to regionally important tubers and cereals, enset is high in calcium, iron, potassium and zinc and low in sodium. We report changes in free amino acid composition due to processing, and establish that the bacteria genera Acetobacter, Lactobacillus and Bifidobacterium, predominate during fermentation. Nutritional and microbial variation presents opportunities to select for improved composition, quality and safety with potentially significant impacts in food security and public health.